Factors that may influence South African nurses' decisions to emigrate - M Oosthuizen; V J Ehlers (AOSIS, 2007)
Although no accurate statistics about the number of South African nurses working in other countries are available, the Organisation of Economic Cooperation and Development estimated that 35 000 South African nurses were working outside South Africa and/or outside the health care system (Horning, 2005:58). Opsomming Alhoewel daar nie akkurate statistiek beskikbaar is oor die aantal Suid-Afrikaanse verpleegkundiges wat in ander lande werk nie, beraam die Organisasie vir Samewerking en Ontwikkeling dat 35 000 Suid-Afrikaanse verpleegkundiges buite Suid-Afrika en/of buite die gesondheidsorgsektor werk (Horning, 2005:58). *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.